Awareness and Perspective of Post-harvest Losses in Vegetable Crops among Agricultural Undergraduates in Sri Lanka - Ekanayake, K.R.B.M.M.K.; Karunadasa, S.H.S.H.; Nayakarathne, N.M.H.I. (University of Jaffna, 2025)
Post-harvest losses in Sri Lanka significantly impact food security and agricultural productivity among vegetable crops, fruit crops, diversified crops and overall crop harvest. The study was aimed to search for awareness and knowledge gaps, providing insight into curriculum reform to raise knowledge, among agricultural undergraduates in Sri Lanka. Despite the growing recognition in awareness of post-harvest losses, there are major gaps in the accuracy of the knowledge and integration of technological advancements in solutions to reduce the loss. A Survey was conducted from December (2024) to February (2025) among agricultural undergraduates studying in their third and fourth year. Data were collected using a self-administered online questionnaire comprising open-ended and closed-ended questions. The study revealed that 93.1% of the respondents were aware and knowledge about post-harvest losses in vegetable crops. Among them majority of 79.4% of the respondents identified poor farmer awareness as the main challenge in reducing post-harvest losses in Sri Lanka. According to the undergraduates’ view, study identified mechanical damage during harvest and post-harvest handling as the major cause of post-harvest loss in vegetable crops. Undergraduates stated that both the government and private sector are effective in addressing post-harvest losses in vegetable crops. However, when they were examined on modern technological integration into post harvest management, the majority (73.5%) stated about cold storage facilities, which shows a considerable knowledge gap among the agricultural undergraduates in Sri Lanka regarding modern technological adaptations. Although their awareness of postharvest vegetable loss increased with their academic exposure. The understanding and recognition level of awareness among the agricultural undergraduates about post-harvest loss influences the direction of future agricultural practices and policy building which positively on food security and sustainability in Sri Lanka’s agriculture post-harvest wastage.
Keywords: Post-harvest loss; Sri Lanka; Undergraduates